1994
DOI: 10.1128/aac.38.5.953
|View full text |Cite
|
Sign up to set email alerts
|

Dextranase enhances antibiotic efficacy in experimental viridans streptococcal endocarditis

Abstract: In endocarditis, exopolysaccharide production by viridans streptococci has been associated with delayed antimicrobial efficacy in cardiac vegetations. We compared the eflicacies of temafloxacin alone and in combination with dextranase, an enzyme capable of hydrolyzing 20 to 90%o of the bacterial glycocalyx, in a rabbit model of endocarditis. In in vivo experiments, rabbits were infected intravenously with 108 Streptococcus sanguis organisms and were treated 6 days later with temafloxacin (50 mg/kg of body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Likewise, the influence of pretreatment duration of infection on the efficacy of antibiotic treatment may be related to the lower metabolic activity of bacteria growing in the vegetation (Cremieux et al, 1993;Entenza et al, 1994). Furthermore, Mghir et al (1994) confirmed the presence of biofilm-compatible structures in the vegetations of rabbits infected with streptococci. The biofilm-like structure was related to dextran production and treatment of the animals with dextranase decreased the infection severity and facilitated antibiotic-induced bacterial eradication.…”
Section: Resultsmentioning
confidence: 73%
“…Likewise, the influence of pretreatment duration of infection on the efficacy of antibiotic treatment may be related to the lower metabolic activity of bacteria growing in the vegetation (Cremieux et al, 1993;Entenza et al, 1994). Furthermore, Mghir et al (1994) confirmed the presence of biofilm-compatible structures in the vegetations of rabbits infected with streptococci. The biofilm-like structure was related to dextran production and treatment of the animals with dextranase decreased the infection severity and facilitated antibiotic-induced bacterial eradication.…”
Section: Resultsmentioning
confidence: 73%
“…Enzymatic digestion of the glycocalyx by dextranase has been shown to enhance the antibiotic activity of penicillin and temafloxacin (33,128).…”
Section: Clinical Applications Of Dextran and Dextranasesmentioning
confidence: 99%
“…Moreover, dextranase has been used in degrading dextran to an appropriate smaller size range suitable for use as a synthetic blood volume expander in patients suffering from hypovolaemic shock 11 . The use of dextranase has also been proposed as a method to increase antibiotic efficacy in infective endocarditis and a universal targeting method for therapeutic agents 12 . Sources of dextranases are widespread: the enzyme has been found in mammalian tissues and in various microorganisms, such as fungi, yeasts, bacteria, and Actinomyces 13,14 .…”
Section: Introductionmentioning
confidence: 99%